Disharmonization of Supreme Court Regulations in Material Judicial Rights - Taufik Hidayat; Resti Dian Luthviati; Suviwat Jenvitchuwong (Journal of Human Rights, Culture and Legal System, 2022)
This study aims to analyze the problems with Supreme Court Regulation in Judicial Review resulting from inconsistencies in these rules, which impact the court's ability to enforce these regulations. This study is a normative legal analysis. The findings of this study indicate that the problem of discordant norms in judicial review is related to two factors, specifically discordant norms regarding the authority to examine formal matters. The discord of norms about the legal subject matter of the Petitioner for Review of Legislation under the Act results from differences in regulation of judicial review material aspect used as a criterion. This contradicts the original intent of the Constitution of the Republic of Indonesia.